Dandelion Sebagai Objek Penciptaan Karya Seni Lukis - Herizqy Herizqy; Erizal Erizal; Armen Nazaruddin (V-art: Journal of Fine Art, 2022)
Dandelion is a flower that comes from Europe and Asia. This flower can regularly release its seeds and is often considered a fruit. The flower head bears many florets, each producing a single seed. Each seed has a parachute that allows it to fly through the air. Five years ago, when still in school, became interested in dandelion flowers. It was the day of the rice harvest, and see the shape of a white ball being swayed by the wind on the edge of the rice fields. Some of the seeds are released and fly in the wind. This event looks so attractive. The approach used is the representational form approach. The techniques used are aquarel, placard, and impasto techniques. The method used is observation, design, and embodiment. First, direct observations were made in the Dandelion flower environment. Then do the design by sketching directly on the canvas. The next stage is the embodiment stage. Cultivation and exploration of techniques on the canvas are carried out until the work is finished. Finally, the presentation is done in the form of an exhibition. The creation of this work succeeded in producing five works entitled “Gelap Ramai,” “Cemas Untung Tenang,” “Cerah dalam Gelap,” “Bolak-Balik,” “Tenang diaduk Senang.”